Time-Space in the Palimpsests of Vasyl Stus (Linguostylistic Studies, 2022)
The article examines the peculiarities of the idiolect of Vasyl Stus based on the case study of his poetry collection Palimpsests. The study is devoted to the means of expressing the notion of time-space. The term time-space is not an absolute synonym for the term chronotope. The term chronotope is used in literature and philosophy. In literary studies, chronotope denotes the chronology of events from the point of view of time, and the location of events from the point of view of place in a work of art. The concept of time-space, in our interpretation, represents the linguistic aspect of the expression of the time-space continuum of the world model and is intended to combine the temporal topos (grammatical interpretation of time), as well as lexical means of time reflection and the linguistic means (lexical and grammatical) of space reflection. Time-space encompasses all forms, means and methods of linguistic representation of the ontology of the world (or its fragment) modelled in an artistic text.The palimpsest in the title of the book is a symbol of a new time-space in the life of the poet and another world of the lyrical hero in the other era. This other era of the lyrical hero is tragic, his world is torn apart, hopes and expectations are destroyed, and the present existence is only suffering and struggle. The core lexeme from the point of view of revealing the ideological and artistic content is the world. The word world itself is defined as the ontology of time-space, but its natural harmony has been destroyed. The study considers the semantic modifications of the lexeme world, which the poet used more than fifty times in the first part of the Palimpsests. The space of the world is created by the concept-images of a cell, a chasm, a ravine, a street, an alley, a pond, hills, a barn, a labyrinth, a cornfield, a valley, a path, Golgotha, heaven, a heavenly height, a kingdom, etc. The flow of world time extends to daylight, night, evening, day, morning, an early time, a season, ages, etc.A large number of language means and their wealth that explicate and imply time-space concepts, their rich imagery and ideological and artistic content is an identifying feature of the poet's idiolect. Further research of them is an interesting aspect in the study of linguopoetics of the texts by Vasyl Stus, who is as immeasurable as the universe.
Keywords: chronotop; idiolect; lingual picture of the world; lexeme; grammeme